2015
DOI: 10.1186/s13071-015-1243-1
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis in Alpine (Rupicapra rupicapra rupicapra) and Apennine (Rupicapra pyrenaica ornata) chamois

Abstract: BackgroundAlthough chamois Rupicapra spp. are the most abundant mountain ungulates in Europe, no data are available on the presence of Giardia duodenalis infecting these species.MethodsA total of 157 fecal samples from Alpine Rupicapra rupicaprarupicapra and Apennine Rupicapra pyrenaicaornata chamois were tested for the presence of G. duodenalis by immunofluorescence test, quantitative Real Time PCR and end-point PCR for genotype characterization.ResultsG. duodenalis was detected in R. r. rupicapra and R. p. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Likewise, no genetic clustering was observed for Giardia isolates from different groups of NHP hosts when compared at the suborder/superfamily level: apes, old world monkeys, new world monkeys and prosimians. There is no clustering of isolates based on host, as has been suggested, for example, with some ungulate isolates within Assemblage A (De Liberato et al., ). Of course, it should be emphasized that although these molecular data indicate the potential for zoonotic/anthropozoonotic transmission, zoonotic risk is impacted by a range of non‐pathogen‐related factors, including the human/animal, their environments and the interaction between these, such as, for example, host ranges, individual host susceptibility under various climates and shared food/water resources (Lal, Hales, French, & Baker, ).…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, no genetic clustering was observed for Giardia isolates from different groups of NHP hosts when compared at the suborder/superfamily level: apes, old world monkeys, new world monkeys and prosimians. There is no clustering of isolates based on host, as has been suggested, for example, with some ungulate isolates within Assemblage A (De Liberato et al., ). Of course, it should be emphasized that although these molecular data indicate the potential for zoonotic/anthropozoonotic transmission, zoonotic risk is impacted by a range of non‐pathogen‐related factors, including the human/animal, their environments and the interaction between these, such as, for example, host ranges, individual host susceptibility under various climates and shared food/water resources (Lal, Hales, French, & Baker, ).…”
Section: Discussionmentioning
confidence: 89%
“…Giardia duodenalis genotyping at the sub-assemblage level allowed us to better identify zoonotic isolates and to define the potential risk of zoonotic transmission in the study area. Previous data showed that AII sub-Assemblage is predominantly found in humans, thus considered zoonotic (Ballweber et al, 2010;Cacciò et al, 2002;Skhal et al, 2017;Sprong et al, 2009), whereas while AIII has been detected in humans only occasionally, also in Italy (Cacciò et al, 2002), infecting preferentially wild hoofed animals (De Liberato et al, 2015;Rafiei et al, 2020;Sprong et al, 2009) and sometimes cats (Lebbad et al, 2010). In our data, a potential risk of zoonotic transmission could be deduced from the clusters obtained in the phylogenetic analysis, which grouped human and cat isolates TA B L E 1 Descriptive analysis and association between direct immunofluorescence assay outcome for Giardia duodenalis and individual and colony variables in cats from central Italy Abbreviation: SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, G. duodenalis and/or Cryptosporidium oo/cysts have been documented in fresh produce in Norway (Robertson and Gjerde, 2001;Robertson et al, 2002) The presence of protozoan oo/cysts in the ready-to-eat samples we investigated is indicative of contamination by feces of human and/or animal origin. In Italy, G. duodenalis Assemblage A and/or C. parvum are widespread among humans (Masucci et al, 2011;Putignani and Menichella, 2010) and animals (both domestic and wild animals) (De Liberato et al, 2015;Giangaspero et al, 2007;Paoletti et al, 2011;Papini et al, 2012), and also in wastewater and shellfish (Giangaspero et al, 2009(Giangaspero et al, , 2014. Cyclospora oocysts (Masucci et al, 2011) or Cyclospora DNA have been recorded not only in humans (Giangaspero et al, 2015a), but also in non-human primates (Marangi et al, 2015), as well as in environmental samples, including vegetables, in the water used to irrigate them (Giangaspero et al, 2015a), and even in tap water (Giangaspero et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%